Multi-Stakeholder Collaboration and Co-Creation in the Implementation of HETERO SPACE (House of Entrepreneurs, Technology-Driven Ecosystem, Resource Optimization, Supportive Programs, Accessible Network, Collaborative Environment) by the Central Java Provincial Office of Cooperatives and Small and Medium Enterprises - Onedha Mawaddah Munzila; Bintoro Wardiyanto (International Journal Labs, 2026)
The Hetero Space innovation (House of Entrepreneurs, Technology-Driven Ecosystem, Resource Optimization, Supportive Programs, Accessible Network, Collaborative Environment) by the Central Java Provincial Cooperatives and Small and Medium Enterprises Office (Dinkop-UKM) is a strategic effort by the Central Java Provincial Government to accelerate business and creative industry collaboration by providing access and learning space for Micro, Small and Medium Enterprises (MSMEs) in Central Java. This study aims to analyze the implementation of collaborative governance in the Hetero Space program within the NPG framework, emphasizing the role of co-creation in the process of creating public value. This study uses a qualitative approach with literature study methods and conceptual analysis to understand the dynamics of interactions between actors in the Hetero Space ecosystem. The results show that Hetero Space represents a collaborative governance practice involving the government, MSMEs, communities and other actors in a structured interaction space. Hetero Space also encourages dialogue, participation, and trust building between actors that form the basis for co-creation. Meanwhile, in the value creation dimension, this program contributes to increasing innovation capacity, expanding networks, and generating public value that is not only economic, but also social.